RANCANG BANGUN SISTEM INFORMASI JASA PERCETAKAN PADA AR PRODUCTION DEPOK - Karnoto Hanif; Trie Hanoto Wibowo (POLITEKNIK LP3I JAKARTA, 2025)
The development of the Printing Services Information System at AR Production is a system for inputting user, product, and invoice data. The user data input system includes customer name, address, mobile phone number, email, password, and level. The product input system includes product name, category, price, and product image. The order input system includes product name, quantity, and price. The main purpose of the Printing Product Ordering System is to make it easier for customers to view products and place orders, while for administrators, it simplifies the management of invoice, product, and user data. The development of this system uses the system development life cycle method. This method involves several stages of the process, namely the system planning stage, system analysis stage, system design stage, system implementation stage, system evaluation stage, and system use and maintenance stage. The Printing Product Ordering System is expected to simplify the process of creating reports for officers so that they can produce accurate and effective data.